Penerapan model pembelajaran inkuiri terbimbing untuk meningkatkan kemampuan berpikir kritis pada pembelajaran IPA di kelas V B SDIT Budi Utomo Jatipurno Wonogiri tahun 2023 - Hidayah, Meiulina; Chumdari, Chumdari; Rintayati, Peduk (Universitas Sebelas Maret, 2026)
This study aims to improve students' critical thinking skills in science learning through the implementation of a guided inquiry learning model. This study is a Class Action Research conducted in two cycles. The research subject is V B students of SDIT Budi Utomo Jatipurno Wonogiri in 2023. Data collection techniques use tests, observations, and interviews. Observation techniques use non-participant observation. The data is analyzed using narrative descriptions and interval values. The results of the study showed an increase in student activity in the classroom. Critical thinking ability increased from pre-cycle 26.1%, cycle I 47.8% to 78.3% in cycle II. Based on the data analysis, it can be concluded that the guided inquiry learning model can improve the critical thinking skills in science learning in V B class of SDIT Budi Utomo Jatipurno Wonogiri in 2023. The implication of this study is that teachers can apply guided inquiry learning model in science learning for fifth grade. Teachers who manage the classroom effectively will positively impact their ability to guide students in developing their critical thinking skills.